Analisis Pengaruh Net Profit Margin, Current Ratio, Debt to Equity Ratio, Company’s Growth, Firm Size, dan Collateralizable Assets terhadap Dividend Payout Ratio (Studi Empiris pada Perusahaan Non Keuangan yang Terdafar di Bursa Efek Indonesia Tahun 2007- - Prasetyo, Fayakun Nur; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2013)
This research was conducted to examine the influence of the company's financial performance through the net profit margin, current ratio, debt to equity ratio, growth, firm size and collateralizable assets of company’s dividend payout ratio in non-financial companies listed inIndonesia Stock Exchange (IDX) in the period 2007 to 2010. Problems of this research is that the contradiction between theory and facts about the effect of net profit margin, current ratio, debt to equity ratio, growth, firm size and collateralizable assets during the observation period in 2007-2010.This research uses secondary data of the non-financial companies which listed on BEI periods 2007-2010. Research sample of 23 non-financial companies, where the method used is purposive sampling, sampling method that takes an object with the specified criteria. The method of analysis used is Multiple Regression with a significance level of 5%. Besides previously also tested the assumption which includes the classical normality test, multicollinearity test, heteroskedastisity test, and autocorrelation test.The results of the research show that Net Profit Margin has positive significant influence to dividend payout ratio and Current Ratio has negative significant influence to dividend payout ratio, while DER, Growth, Firm Size, and Collateralizable Assets have no influence to dividend payout ratio. All of this variable significant effected the value simultaneously, with the sum of the effect was 12,5%